NGIKIS Traditional Ceremony in Ciamis Regency (Study of Meaning, Value of Local Wisdom and Its Relevance in Historical Learning at MAN 2 Ciamis) - Hidayatuloh, Sarip; Musaddad, Ahmad Arif; Ediyono, Suryo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Ngikis traditional ceremony is one form of local wisdom in Ciamis Regency which until now is still done, considering the people of Karangkamulyan believe there is a charge of meaning and values in it. The meaning and values of local wisdom, have relevance to the learning of History in MAN 2 Ciamis. The purpose of this study is to describe and explain: (1) meaning; (2) local values of wisdom; and (3) relevance of the values of local wisdom of Ngikis traditional ceremonies Ngikis traditional ceremony with history learning at MAN 2 Ciamis. The method used in this study is a qualitative method with an ethnographic approach. The data collection technique performed is 1) Observation; 2) Interview; and 3) Documentation. The results showed: 1) the meaning of the Ngikistraditionalceremony, namely: as a form of respect for the ancestors of public Karangkamulyan, and also as a means to the fence and cleanse themselves from all despicable traits, then as an expression of gratitude to God YME for the sustenance that has been given; 2) the values of local wisdom, including values: religious, social, history, culture, ethics, and compassion, compassion,  Admission; 3) relevance of  Ngikis traditional ceremonies to Historical learning, which can create learning based on local culture and educational value in MAN 2 Ciamis